2017
DOI: 10.1158/1541-7786.mcr-17-0241
|View full text |Cite
|
Sign up to set email alerts
|

Notch Represses Transcription by PRC2 Recruitment to the Ternary Complex

Abstract: It is well established that Notch functions as a transcriptional activator through the formation of a ternary complex that comprises Notch, Maml and CSL. This ternary complex then serves to recruit additional transcriptional cofactors that link to higher order transcriptional complexes. The mechanistic details of these events remain unclear. This report reveals that the Notch ternary complex can direct the formation of a repressor complex to terminate gene expression of select target genes. Herein, it is demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Upon activation through cell-to-cell interaction, the Notch intracellular domain is released from the cell membrane and translocates to the nucleus, where it initiates the formation of a ternary complex with Maml and CSL (3,4). It is thought that this ternary complex serves as a scaffold to recruit additional transcriptional coactivators to drive a Notch-dependent transcriptional cascade (5)(6)(7)(8). Therefore, deregulation of Notch leads to the aberrant enforcement of a transcriptional profile that drives a neoplastic program (3,4,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation through cell-to-cell interaction, the Notch intracellular domain is released from the cell membrane and translocates to the nucleus, where it initiates the formation of a ternary complex with Maml and CSL (3,4). It is thought that this ternary complex serves as a scaffold to recruit additional transcriptional coactivators to drive a Notch-dependent transcriptional cascade (5)(6)(7)(8). Therefore, deregulation of Notch leads to the aberrant enforcement of a transcriptional profile that drives a neoplastic program (3,4,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, we brought insight into how the NOTCH1-HES1 pathway was regulated by miR-137. LSD1 has been linked to the repression of NOTCH1 pathway in various cell types [45,[59][60][61][62][63], though one study states that it functions as a corepressor when associated with RBPJ-repressor complex and as a NOTCH1 coactivator upon NOTCH activation [64]. Nevertheless, few studies have reported the interplay between NOTCH1 and LSD1 during the osteogenesis of hASCs and whether this interaction contributes to the osteogenic regulation of miR-137 is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Han lymphomas, and along with the ternary complex forms a stable transcriptional repressor complex. This leads to enrichment of H3K27me3 repression and loss of H3K4me3 activation, contributing to downstream repressive epigenetic changes [133]. In addition, preliminary data showed that Notch activation led to direct EZH2 and SUZ12 transcriptional induction, although no evidence has shown that they are direct Notch-target genes [133].…”
Section: Prc2 Loss and Notch Signalingmentioning
confidence: 99%
“…This leads to enrichment of H3K27me3 repression and loss of H3K4me3 activation, contributing to downstream repressive epigenetic changes [133]. In addition, preliminary data showed that Notch activation led to direct EZH2 and SUZ12 transcriptional induction, although no evidence has shown that they are direct Notch-target genes [133]. Intriguingly, there is also interplay between RAS signaling and Notch signaling; in this manner, Notch signaling seems to be downstream of oncogenic RAS, and wildtype Notch1 is needed for oncogenic RAS-mediated neoplastic transformation of human cells in vitro and in vivo [134].…”
Section: Prc2 Loss and Notch Signalingmentioning
confidence: 99%